Replacing carbohydrate with protein and fat in prediabetes or type-2 diabetes: greater effect on metabolites in PBMC than plasma. Issue 1 (December 2016) - Kim, Minjoo; Song, Gayoung; Kang, Miso; Yoo, Hye; Jeong, Tae-Sook; Lee, Sang-Hyun; Lee, Jong
Abstract Background Active metabolism of peripheral blood mononuclear cells (PBMC) could suggest their suitability for metabolomics studies. This study examined whether reductions in PBMCs and plasma lipoprotein-associated phospholipase A2 (Lp-PLA2 ) activities induced by dietary intervention affected the overall metabolic profiles of PBMC and plasma. Methods Eighty nonobese subjects aged 40–70 years (18.5 ≤ BMI < 30 kg/m2 ) with prediabetes or newly-diagnosed type-2 diabetes were assigned to consume either the usual refined-rice diet (control group, n = 40) or to replace refined rice with whole grains and legumes as carbohydrates (whole-grain group, n = 40) for three meals per day during the 12-week intervention. Fasting PBMC and plasma metabolomes were profiled using UPLC-LTQ-Orbitrap mass spectrometry. Results After 12 weeks, changes in fasting glucose, HbA1c, HOMA-IR, MDA, ox-LDL, LDL particle size, plasma Lp-PLA2 activity, and PBMC enzyme activity in the whole-grain group were significantly different from those in the control group before and after adjusting for baseline levels. The PBMC levels of L-leucine, oleamide, lysoPC (16:0), and lysoPC (18:0) in the whole-grain group showed greater reductions compared with those of the control group. Changes in plasma metabolites were not significantly different between the two groups. Changes in PBMC Lp-PLA2 activity positively correlated with changes in L-leucine, oleamide, lysoPC (16:0), lysoPC (18:0), glucose, and ox-LDL, and negatively correlated with changes in LDL particle size. Conclusions This study showed that dietary intervention in prediabetic or type-2 diabetic patients had a greater effect on PBMC Lp-PLA2 activity and metabolites compared with those of plasma metabolites. Trial registration NCT02191644